Teachers’ Perceptions and the Effectiveness of Syllabus Use and Lesson Plan Implementation Through Collaborative Planning - Musdalifah, Musdalifah (ETDC: Indonesian Journal of Research and Educational Review, 2025)
The syllabus and lesson plan play significant roles in the success of a teacher's instruction. The regulation of the Indonesian government has required teachers to design lessons in the form of a syllabus and lesson plan. Madania School, particularly in the Lower Secondary Department, has supported teachers by organizing lesson plan meetings to help them apply the government program. The aims of this study were to find out how the lower secondary teachers in Madania School Makassar perceive a curriculum, which is a syllabus and lesson plan; how the syllabus is effectively used in a lesson plan meeting; and how the lesson plan is effectively implemented in the classroom. The study applied mixed-method research, which examined the perception of teachers on the function and effectiveness of the syllabus and lesson plan, measured the effectiveness of the usage of the syllabus in the lesson plan meeting, and measured the effectiveness of lesson plan implementation in the classroom. The research was conducted in grades 7 and 8 at Madania Lower Secondary School of Makassar. The research finds that lesson plan meetings enable the teachers to discover various activities to do in the class. But since not all lesson plan components are used in class, there is no strong link between lesson plan implementation and teachers' views of the curriculum.